Car ownership and the labor market of ethnic minorities - Pieter A. Gautier; Yves Zenou (Institute for the Study of Labor (IZA), 2008)
We show how small initial wealth differences between low skilled black and white workers can generate large differences in their labor-market outcomes. This even occurs in the absence of a taste for discrimination against blacks or exogenous differences in the distance to jobs. Because of the initial wealth difference, blacks cannot afford cars while whites can. Car ownership allows whites to reach more jobs per unit of time and this gives them a better bargaining position. As a result, in equilibrium, blacks end up with both higher unemployment rates and lower wages than whites. Furthermore, it takes more time for blacks to reach their jobs even though they travel less miles. Those predictions are consistent with the data. Better access to capital markets or better public transportation will reduce the differences in labor market outcomes.
urn:nbn:de:101:1-20081127369
Keywords: D83; 330; Transportation mismatch; job search; spatial labor markets; multiple job centers; ethnic minorities; Arbeitsuche; Arbeitsmarktdiskriminierung; Farbige Bevölkerung; Berufsverkehr; Kraftfahrzeug; Vermögensverteilung; Regionaler Arbeitsmarkt; USA